Upaya Mengurangi Rendahnya Minat Literasi pada Siswa Kelas 6 SDN Plerean 2 Kabupaten Jember - Mutmainnah, Mutmainnah; Agustin, Erninda Puji; Setianto, Bayu; Balya, Dhanial; Allam, Daffa` Abiyyu Sulthan; Daniaturrohman, Fida; Wardana, Hengky; Meylani, Dian; Mahbubah, Zaitun; Arifin, Irman; Sunarko, Viandra Rafelia Cahya; Rohman, Irsyad Zaki; Laily, Faikhatul; Ramadani, Fitria Ayu; Kurniawati, Nani (UNIB Press, 2024)
The